Love and Theatre in the Works of Nikephoros Basilakes - Kotłowska, Anna (Studia Ceranea, 2019)
The article analyzes the rhetorical output of Nikephoros Basilakes, focusing on his use of scenic terminology and the psychological interpretation of myths. The conclusions substantiate the theory that Nikephoros had been part of the imperial theatron before his downfall in the mid-1150s.